Principal Leadership in the Implementation of Effective School Management - Sunaengsih, Cucun; Anggarani, Mayang; Amalia, Mia; Nurfatmala, Silmaulan; Naelin, Syifa Diana (Universitas Pendidikan Indonesia, 2019)
This research aims at describing the implementation of effective school management based on the principal leadership in one of Public Primary Schools in Sumedang Regency, West Java, Indonesia. The principal who implemented effective school management had the potential to produce high-achieving young generation because the school scope could optimize its function as an educational institution that carried out economic, humanitarian, social, political, cultural, and educational functions. One aspect that could support the implementation of effective school management was the principal leadership in making decisions, communicating, directing and developing the staff, solving problems and evaluating school activities. The data were collected through questionnaires, interviews and documentation studies. Furthermore, the results proved that the principal leadership was one of the main factors in implementing effective school management in terms of technology, school culture, information systems, and organizations.